Thin endometrium - combined non-hormonal treatment during the process of preparing to the IVF program - M G Schneiderman; E A Kalinina; V Yu Smolnikova; N G Mishieva; A N Abubakirov; L A Levkov; K U Alieva; A G Bykov; A A Kuzemin; E V Dyuzheva; L M Kazaryan; S V Pavlovich; et al. (IP Berlin A.V., 2014)
The thin endometrium often turns out to be the cause of the considerable decrement of the pregnancy after the IVF procedure. It is considered that the endometrium thickness which is less than 7 mm (in the implantation window) provides the minimal chance for the efficient conception. Up to the present time in the modern scientific literature we did not found any facts about the treatment of the patients with the thin endometrium by means of the gas mixture (CO2 and N2) processing of the endometrium, which provides the considerable blood circulation enhancement combined with gynecological massage and, as a result, the rising of the thickness of the basal and functional layers. We are recommend this method as a preparing women for IVF.